Currently Available Non-Balloon Devices - Hang Lak Lee (Clinical Endoscopy, 2018)
Obesity and metabolic syndrome are known to have an impact on the economy. Obesity and metabolic syndrome affect about 40% population in the America alone, and with about 400 million obese adults in the world, obesity is a global concern. Moreover, the prevalence of overweight children is increasing. Bariatric surgery remains the gold standard for the treatment of obesity; however, endoscopic approaches may have a significant role in the management of metabolic syndrome and obesity. Until recently, many endoscopic methods have been introduced; however, few methods are used in practice, whereas others are under experimental research. Endoscopists have an important role in the treatment of obesity because endoscopic therapies have demonstrated their safety and efficacy over the past few years. Endoscopic bariatric therapies can be categorized as follows: space occupying, malabsorption, and gastric volume reduction. In this review, we summarize the currently available non-balloon type endoscopic procedure.